2013
DOI: 10.1007/s00535-013-0915-x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and pancreatic cancer: disease promoter and new therapeutic target

Abstract: Chronic inflammation has a certain impact on the carcinogenesis of the digestive organs. The characteristic tissue structure of pancreatic cancer, desmoplasia, results from inflammatory processes induced by cancer cells and stromal cells. Concerning the progression of pancreatic cancer, recent research has clarified the pivotal role of tumorstromal interaction, which promotes the development of an invasive phenotype of cancer and provides survival advantages against chemotherapeutic agents or immune surveillan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 116 publications
0
34
1
Order By: Relevance
“…The current study compared tumor with adjacent benign pancreatic tissues from the same PDAC patients. The upregulation of antigen presenting molecules reflect an inflammatory feature of the PDAC [35, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…The current study compared tumor with adjacent benign pancreatic tissues from the same PDAC patients. The upregulation of antigen presenting molecules reflect an inflammatory feature of the PDAC [35, 36]. …”
Section: Discussionmentioning
confidence: 99%
“…The desmoplastic stroma in the microenvironment of pancreatic cancer plays an important role in the progression of tumors and can recruit inflammatory cells, such as macrophages . The previous studies have shown that macrophages, particularly for M2 cells, are crucial for the pathogenesis of pancreatic cancer . In this study, we examined the potential effect of pancreatic cancer cell interaction with U937ā€derived macrophages and M2 cells on the differentiation and function of macrophages and on the behaviors of PDAC in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, human pancreatic cancer tissue exhibits significant infiltration by immune cells such as T cells, B cells, NK cells, neutrophils, and macrophages as well as myeloid-derived suppressor cells (as the name suggests, MDSCs have a largely immunosuppressive function) [128,[143][144][145]. Yet, pancreatic cancer cells appear to be able to successfully evade any attacks from these immune cells.…”
Section: In Vivo Studiesmentioning
confidence: 92%
“…The desmoplastic reaction in PDAC is known to contain a prominent immune cell infiltrate [128,[143][144][145] but these cells appear to be unable to exert their immunogenic effects to destroy cancer cells. There is some evidence to suggest that PSCs may aid the process of immune evasion by cancer cells.…”
Section: Psc-immune Cell Interactionsmentioning
confidence: 98%